PERENCANAAN ENTERPRISE ARCHITECTURE REKRUTMEN ANGGOTA PANTARLIH (PANITIA PEMUTAKIRAN DATA PEMILIH) DAN KPPS (KELOMPOK PENYELENGGARA PEMUNGUTAN SUARA) PADA DESA MAJINGKLAK MENGGUNAKAN ZACHMAN FRAMEWORK - Warlianingsih Kartikasari, Syndah; Mulyana, Dadan; Yudi Permana, Nana (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2025)
Elections in Indonesia are held every five years. Election organizers are divided into two groups: the permanent General Election Commission (KPU) and the temporary (Ad Hoc) committees (PPK, PPS, KPPS), and the Pantarlih (General Election Committee). These committees serve only during the election process and can then be selected at the next level. The Pantarlih (Voter Data Update Committee) is responsible for verifying and scrutinizing voter lists to ensure their accuracy. The KPPS (Voting Organizing Group) is responsible for collecting and counting votes at polling stations (TPS). Currently, the PPS still manually recruits Pantarlih and KPPS members in Majingklak Village. The selection process involves direct coordination with the local hamlet head to directly select members based on subjective assessments. This creates problems, as registration information is not widely disseminated, leading to social jealousy in the community, and selected members do not meet the criteria. To address this issue, a web-based recruitment system is needed for Pantarlih and KPPS members. The results of this study are a blueprint for the recruitment of Pantarlih (Election Committee) and KPPS (Election Working Group) members using the Zachman Framework, which includes four planning stages: Scope/Contextual, Business Process, System Model, and Technology Model. This system is expected to provide solutions to problems in the recruitment process for Pantarlih and KPPS members and assist the PPS in decision-making to select qualified Pantarlih and KPPS members.